EMERGING ISSUES IN THE DEVELOPMENT OF AGRITOURISM IN INDONESIA: A BIBLIOMETRIC ANALYSIS - Nirwikara Widhiwidhana Prasetyanto; Iwan Setiawan; Endah Djuwendah; Suhartini Suhartini (Universitas Sebelas Maret, 2025)
Indonesia possesses significant potential for agritourism development,supported by its abundant natural resources, cultural richness, and largeagricultural workforce. Despite this, various challenges—such as limitedinfrastructure, insufficient farmer skills, weak promotion, and poor stakeholdercollaboration—continue to impede progress. This study analyzes existingliterature on agritourism in Indonesia using a qualitative content analysisgrounded in bibliometric data. The analysis draws on Scopus-indexedpublications from 2014 to 2025, retrieved using keywords: (“Agritourism” or“Agro-tourism” or “Agrotourism” or “Farm tourism” or “Agricultural tourism”)and “Indonesia”. The data were processed with VOSviewer and Biblioshiny toexamine keyword relationships, publication trends, and emerging researchthemes. Results show Indonesia is the second most studied country inagritourism, with 94 articles—after the United States (181) and Italy (106). Anotable increase in publications was observed post-COVID-19 (2020–2025).Following abstract screening, 78 relevant articles were included in thebibliometric analysis. Co-occurrence analysis identified five main keywordclusters, reflecting the dominant themes in the field. The study synthesizes theseclusters to outline the conceptual structure of agritourism research in Indonesia.Findings suggest that future studies should focus on enhancing communityparticipation in development of agritourism.